Meta-Analysis ELECTRE III and AHP in Evaluating and Ranking the Urban Resilience - KOSOVA, Robert; QENDRAJ, Daniela Halidini; XHAFAJ, Evgjeni (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).15, 2022)
Recently, climate change has become more visible, with weather extremes and natural disasters causing more economic damage than ever before. Given all the factors that threaten the dynamic ecological balance, it is very important to ask whether there is a possibility to assess the sustainability of some territorial units using technical and scientific criteria. Is there a method to assert that one community or municipality is more resilient than another and to explain all of this? Multi-criteria decision analysis (MCDA) is the most appropriate theory best applied to such complex decisions. MCDA methods are used to assess "if and how resilient my city is". Previous methodological frameworks for urban sustainability have been created and presented in the literature, and most of them use the AHP technique. These methods form a hierarchy of decision-making problems with criteria and alternatives (cities, communities), and the latter are evaluated based on how well they meet the criteria. This paper aims to assess the urban resilience of Durres County, Albania, and its regions and municipalities that share the same urban and geographical characteristics using the AHP and Electre III methods. This city has been studied, analyzed, and evaluated because it has a history of natural disasters and is in a very dangerous area for some indicators. The results of the study concluded that the district, its regions, and communes are at high risk of flooding due to torrential rains accompanied by river floods, erosion of agricultural lands and the coast, as well as other natural risks, and need significant improvements to cope with them. Albania and the region of Durres have been involved over the years in several national and international projects to improve urban sustainability and resilience. However, the assessment and improvement of urban sustainability should always be an ongoing process.